The histidine phosphotransfer AHP4 plays a negative role in Arabidopsis plant response to drought. (23rd August 2022) - Ha, Chien Van; Mostofa, Mohammad Golam; Nguyen, Kien Huu; Tran, Cuong Duy; Watanabe, Yasuko; Li, Weiqiang; Osakabe, Yuriko; Sato, Mayuko; Toyooka, Kiminori; Tanaka, Maho; Seki, Motoaki; Burritt, David J.; et al.
SUMMARY: Cytokinin plays an important role in plant stress responses via a multistep signaling pathway, involving the histidine phosphotransfer proteins (HPs). In Arabidopsis thaliana, the AHP2, AHP3 and AHP5 proteins are known to affect drought responses; however, the role of AHP4 in drought adaptation remains undetermined. In the present study, using a loss‐of‐function approach we showed that AHP4 possesses an important role in the response of Arabidopsis to drought. This is evidenced by the higher survival rates of ahp4 than wild‐type (WT) plants under drought conditions, which is accompanied by the downregulated AHP4 expression in WT during periods of dehydration. Comparative transcriptome analysis of ahp4 and WT plants revealed AHP4‐mediated expression of several dehydration‐ and/or abscisic acid‐responsive genes involved in modulation of various physiological and biochemical processes important for plant drought acclimation. In comparison with WT, ahp4 plants showed increased wax crystal accumulation in stems, thicker cuticles in leaves, greater sensitivity to exogenous abscisic acid at germination, narrow stomatal apertures, heightened leaf temperatures during dehydration, and longer root length under osmotic stress. In addition, ahp4 plants showed greater photosynthetic efficiency, lower levels of reactive oxygen species, reduced electrolyte leakage and lipid peroxidation, and increased anthocyanin contents under drought, when compared with WT. These differences displayed in ahp4 plants are likely due to upregulation of genes that encode enzymes involved in reactive oxygen species scavenging and non‐enzymatic antioxidant metabolism. Overall, our findings suggest that AHP4 plays a crucial role in plant drought adaptation. Significance Statement: Loss‐of‐function analysis of the cytokinin signaling member Arabidopsis histidine phosphotransfer protein 4 revealed its negative role in Arabidopsis adaptation to drought, affecting various physiological and biochemical processes by modulating the expression of a large set of genes, including abscisic acid‐responsive genes.